Finger flexor force influences performance in senior male air pistol Olympic shooting - Mon, D.; Zakynthinaki, M. S.; Cordente, C. A.; Monroy Anton, A. J.; Rodriguez Rodriguez, B.; Lopez Jimenez, D. (PLOS ONE, 2015)
The ability to stabilize the gun is crucial for performance in Olympic pistol shooting and is thought to be related to the shooters muscular strength. The present study examines the relation between performance and finger flexor force as well as shoulder abduction isometric force in senior male air pistol shooting. 46 Spanish national level shooters served as test subjects of the study. Two maximal force tests were carried out recording handgrip and deltoid force data under competition conditions, during the official training time at national Spanish championships. Performance was measured as the total score of 60 shots at competition. Linear regressions were calculated to examine the relations between performance and peak and average finger flexor forces, peak and average finger flexor forces relative to the BMI, peak and average shoulder abduction isometric forces, peak shoulder abduction isometric force relative to the BMI. The connection between performance and other variables such as age, weight, height, BMI, experience in years and training hours per week was also analyzed. Significant correlations were found between performance at competition and average and peak finger flexor forces. For the rest of the force variables no significant correlations were found. Significant correlations were also found between performance at competition and experience as well as training hours. No significant correlations were found between performance and age, weight, height or BMI. The study concludes that hand grip strength training programs are necessary for performance in air pistol shooting.